Perancangan User Experience Aplikasi Portal Smart City Kota Malang dengan Metode Pendekatan Human-Centered Design - Lina Fitra; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The lack of public awareness about the existence of government online services is partly due to its spread on different platforms. By utilizing information technology, applications are seen as solutions that can accommodate various government services to be easier accessed by public. This study aims to design a good user experience using Human-Centered Design (HCD) approach in order to ease people in using government services. Context of use analysis is done by conducting interviews with Dinas Komunikasi dan Informatika Kota Malang as the stakeholder. The second phase, user needs analysis, is carried out by analyzing the results of interviews with stakeholders and users in order to obta in the content needs. Then, producing design solutions is carried out by implementing the results of the analysis in to the form of storyboard, user flow, information architecture, wireframe, screenflow, mockup, and prototype. The last phase, design evaluation, is carried out through usability testing with five users in three iterations. Effectiveness aspect measured by the completion rate shows a stable success rate of 100%. The efficiency aspect which is measured by calculating time-based efficiency is scored 0.0189goals/sec. The satisfaction aspect is measured using single ease question and got a final score of 6. Through usability testing, problems are also found in the design solutions which are then fixed in each iteration.